The Relationship Between Perceptions of Overprotective Parenting and Stress in Middle Adolescents in Yogyakarta (Journal of Social And Education Research, 2023)
Middle adolescence is a transitional phase from childhood to adulthood, characterized by various physical, psychological, and social changes. These changes may lead to stress. One factor influencing stress is parenting style, particularly overprotective parenting. Overprotective parenting can shape adolescents’ perceptions, which may affect the level of stress experienced. This study aims to examine the relationship between perceptions of overprotective parenting and stress among middle adolescents in Yogyakarta. This quantitative correlational study involved 128 middle adolescents in Yogyakarta, selected using purposive sampling. Data were collected using overprotective parenting perception scales and stress scales, then analyzed using the Pearson Product Moment correlation. Most respondents reported moderate stress levels (71.1%) and moderate perceptions of overprotective parenting (77.3%). Pearson correlation analysis showed p = 0.000 (p < 0.05) with a correlation coefficient of r = 0.249, indicating a weak but significant positive relationship between perceptions of overprotective parenting and stress.There is a significant positive relationship between perceptions of overprotective parenting and stress in middle adolescents. Adolescents experiencing overprotective parenting are encouraged to remain resilient and find meaningful lessons from their experiences.